Efektivitas Kontribusi Pajak Reklame dalam Meningkatkan Pendapatan Asli Daerah Kota Palembang - Amrul Mukminin; Alamsyah Alamsyah; Mega Nugraha (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Amrul Mukminin. This study aims to analyze the Effectiveness of the Advertising Tax Contribution in Increasing Local Revenue in Palembang City. This research uses qualitative methods with data observation techniques, interviews and documentation. The results showed that the advertisement tax management was an effort to increase PAD in Palembang City, to someone who was trying to be managed properly. However, there are indeed several problems where the supervision and participation of the community with illegal billboards is still happening and the implementation of regional regulations is not running properly, therefore the PAD from the advertisement tax has not been maximized. The supporting factor in this research is the availability of Palembang mayor regulation number 18 of 2011 concerning requirements, and fixed procedures for collecting advertisement tax and then Palembang City Regional Regulation Number 8 of 2004 concerning Development and Retribution for Advertising. In addition, to support the vision, mission and strategic plans of the Tax Management Agency. Two things support the effectiveness of the advertisement tax contribution. Internal and external factors inhibiting factors. Obstacles in internal factors, for example, the application of sanctions for billboards arrears who have just appeared without the knowledge of the officers, and the lack of socialization from the Regional Tax Management Agency so that the public does not know about the existence of regional regulations regarding advertisement tax. Whereas in external factors, for example, the community's low awareness of paying taxes or they tend to avoid and are dishonest in the report on the results of the installation of billboards and taxpayers who live outside the city of Palembang.